Research on the Relationship between Tibetans' Degree of Religious Devotion and Their Tendency to Work in Other Regions - Zhou, Lihaolin (International Journal of Social Sciences and Public Administration, 2024)
In recent years, the Tibetan people have made many contributions to safeguarding national unity. They contribute to the promotion of Chinese culture through joint efforts. This study examines the relationship between a Tibetan's degree of religious devotion and his propensity to work in other Chinese provinces. First, this article reviews the relevant literature, focusing on the relationship between the spatial patterns of ethnic minority settlements and the location of religious sites. Second, a questionnaire survey was conducted on this research topic. Chi-square is used to analyze data to determine if two variables are independent. In addition, this article analyzes the advantages and disadvantages of survey strategies. To sum up, the survey results are convincing and can provide references for related studies.